Theft is property! : dispossession & critical theory - Nichols, Robert, 1979- (Radical Américas., 2020)
"In THEFT IS PROPERTY! Robert Nichols develops the concept of "recursive dispossession" to describe the critical bind that Indigenous activists face when seeking justice for the appropriation of their land: they simultaneously claim that their land was stolen by Anglo settlers, but also that territoriality and property ownership are themselves settler concepts. Putting Indigenous thought into conversation with Marxist theory, Nichols argues that property relations under settler colonialism are built upon a structural form of negation, wherein some groups must be alienated from the very property that is being created. Thus, theft precedes and generates property, rather than vice versa, and Indigenous claims of retroactive "original ownership" are not contradictory or logically flawed, but rather, gesture back to this very dynamic. By looking at dispossession as a unique historical process in the context of colonialism, Nichols shows how contemporary Indigenous struggles have always already produced their own mode of critique and articulation of radical politics"--